Correlates of bitter, sweet, salty and umami taste sensitivity in European children: Role of sex, age and weight status - The IDEFICS study. (1st August 2022) - Jilani, Hannah; Intemann, Timm; Buchecker, Kirsten; Charalambos, Hadjigeorgiou; Gianfagna, Francesco; De Henauw, Stefaan; Lauria, Fabio; Molnar, Dénes; Moreno, Luis A.; Lissner, Lauren; Pala, Valeria; Siani, Alfonso; et al.
Abstract: We aimed to describe differences in taste sensitivity in children according to age across 7- to 11-year-old children from eight European countries. We further compared taste sensitivity between boys vs. girls and under-/normal weight vs. overweight/obese children. Within the European multicentre IDEFICS (Identification and prevention of dietary and lifestyle-induced health effects in children and infants) study, 1938 school children participated in sweet, bitter, salty and umami detection threshold tests between 2007 and 2010, using the paired comparison staircase method. The lowest concentration at which the child was able to detect a difference to water was determined as taste detection threshold as a proxy of taste sensitivity. Mean taste thresholds were calculated stratified for sex, age groups, weight groups and country. BMI was calculated using measured height and weight; socio-demographic information was collected using questionnaires. Ordinal logistic regressions were conducted to investigate the association between sex, weight status (as categorical exposure variable) and age (as continuous exposure variable) and the taste sensitivity for the four taste modalities (as outcome), separately. Older children were more taste sensitive for sweet and salty and less taste sensitive for umami and bitter than younger children. Girls were more sensitive to sweet taste than boys. Overweight or obese children were less sensitive to sweet and salty taste compared to normal weight children This was the first study comparing taste sensitivity by measuring taste thresholds in children across different European countries. We conclude that taste thresholds are associated with weight status, children become more sensitive to sweet and salty tastes with increasing age, and girls might be more sensitive to sweet than boys.